Distinct Perspective of Uterine Prolapse with special reference to its Etiological Factor and Treatment - Shivde, Neha; Kore, Sharayu (International Research Journal of Ayurveda & Yoga, 2022)
Uterine prolapse (UP), also known as pelvic organ prolapse (POP) and genital prolapse, describes the descent of the uterus from its normal anatomical confines to positions within or outside the vaginal introitus. Etiological factors for prolapse vary from study to study but those reported consistently are increasing age, parity and obesity. Other possible causes include smoking, chronic increase in intra abdominal pressure, estrogen deficiency; connective tissue disorders, low socioeconomic status, ethnicity and family history. This article is a case study which represents, raised internal abdominal pressure due to YOG activities like Kapalbhati as a causative factor of uterine prolapse and accordingly the treatment plan. At present people are practicing Yog, Pranayam & Asana. But it is important to remember that the activities appropriate for some women may not be suited to others depending on individual risk factors for pelvic floor injury. In Ayurved, treatment plan changes from person to person depending upon NIDAN PANCHAK (Diagnostics) that is 1. Etiological factors 2. Premonitory Symptoms 3. Signs & Symptoms 4. Pacifying & Aggravating factors 5. Individualized pathogenesis of disease. Thus, it is not sufficient to treat such cases with disease specific treatment, but investigating etiological factor and planning of treatment accordingly is worthwhile.